Workaholism and family interaction among nurses - Borges,Elisabete Maria das Neves (2021)
Abstract This study aims to identify the prevalence of workaholism and work-family interaction, their relationship and their variation according sociodemographic and occupational characteristics among nurses. A quantitative, descriptive, correlational and transversal study was conducted with a sample of 839 Portuguese nurses. Regarding workaholism, 27% of workaholic nurses were identified, scoring a higher mean value for excessive work. For work-family interaction, the dimensions showing the highest mean values were the negative work-family interaction and the positive family-work interaction. The variables identified as significant predictors of workaholism were the work-family interaction (39%), occupational variables (10.6%) and sociodemographic variables (1.2%). Among the occupational and professional variables, the women, age equal or less than 37 years and perception of stressful work, were highlighted. The confirmation of workaholism in nurses, as well as its predictive variables are significantly important for professionals and organizations to better understand the impact of this phenomenon, particularly in mental health and to encourage the development of programmes aiming to promote health at the workplace.